Benzyl N-[1-(thiophen-2-yl)ethylidene]-hydrazinecarbodithioate - Chan, Mun-Hoe Eddy; Crouse, Karen A.; Tarafder, M. T. H.; Yamin, Bohari. M. (2003)
In the title compound, C14H14N2S 3, the benzyl and 1-(thiophen-2-yl)ethylideneamine groups are cis and trans to the thiono S atom across the C-S and C-N bonds, respectively. The dithiocarbazate plane makes dihedral angles of 9.14 (6) and 85.40 (8)° with the thiophenemethyleneamine and benzyl fragments, respectively. In the crystal structure, the molecules are linked by N-H⋯S hydrogen bonds between the amino group and the thiono S atoms and are arranged as dimers parallel to ab face. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.